The relationship between skin ultrasound images and muscle damage using skin blotting in wheelchair basketball athletes - Tamai, N.; Minematsu, T.; Maeda, T.; Yabunaka, K.; Sanada, H. (Spinal Cord, 2020)
Study design: Secondary analysis of a cross-sectional observation study. Objectives: To determine the relationship between skin ultrasound images and muscle damage in wheelchair basketball athletes, using skin blotting examinations of the ischial regions. Setting: Community, Japan. Methods: Fourteen elite wheelchair basketball athletes were recruited. We obtained data regarding participants` characteristics. We undertook ultrasonographic images and quantitative skin blotting of the ischial region before and after training, and after rest. Results: We identified Category II and III pressure injuries in 2 of the 12 participants. Structural features were classified into four categories based on ultrasonographic features, namely, normal skin structure, unclear superficial and deep fascia, cloudy fat layer, and fat infiltration and low-echoic lesion/anechoic lesions. The muscle-type creatinine kinase (CK-M) level (median [interquartile range: IQR], 2.98 [2.80-3.47]) in the fat infiltration and low-echoic lesion/anechoic lesion group was significantly higher (1.43 [1.41-1.49]) than in a nonfat infiltration and low-echoic lesion/anechoic lesion group after training (p = 0.03). The interleukin-6 (IL-6) level (median [IQR], 23.5 [16.15-58.97]) in the fat infiltration and low-echoic lesion/anechoic lesion group was significantly higher (1.94 [1.74-4.44]) than in the nonfat infiltration and low-echoic lesion/anechoic lesion group after rest (mean difference = -25.4, 95% CI -61.1 to 10.7, p = 0.03). Conclusions: The combination of ultrasonographic images and skin blotting using CK-M and IL-6, could detect early deep tissue damage in wheelchair athletes. These techniques could be potentially useful in the treatment and prevention of pressure injuries.